Domain Structure of a Unique Bacterial Red Light Photoreceptor as Revealed by Atomic Force Microscopy. Issue 1652 (27th February 2014) - Sorenson, Blaire A.; Westcott, Daniel J.; Sakols, Alexandra C.; Thomas, J. Santoro; Anderson, Perry; Stojković, Emina A.; Tsonchev, Stefan; Nicholson, Kenneth T.
ABSTRACT: Bacteriophytochromes (BphPs) are red-light photoreceptors found in photosynthetic and nonphotosynthetic bacteria that have been recently engineered as infrared fluorescent tissue markers. Light-induced, global structural changes are proposed to originate within their covalently bound biliverdin chromophore and propagate through the protein. Classical BphPs undergo reversible photoconversion between spectrally distinct light absorbing states, red (Pr) and far-red (Pfr), respectively. RpBph3 (P3), from Rhodopseudomonas palustris, photoconverts between a Pr and a unique near-red (Pnr) light-absorbing state. Due to size and photosensitivity of BphPs, structures of the intact proteins have not been resolved by nuclear magnetic resonance and/or X-ray crystallography. Therefore, structural details about the light and dark-adapted structures of the intact BphPs are not well understood at the molecular level. We have utilized fluid cell atomic force microscopy (AFM) to investigate the domain structure of intact P3 in its light-adapted state (Pnr). By varying the concentration of the protein, deposition time, and the ionic strength of the buffer, the aggregation of P3 on a mica surface can be controlled and single dimers may be observed in a biologically relevant media. Domain resolution has been achieved for several orientations of the dimer on the surface. The structural dimensions of the dimer have been compared to a modeled BphP in its intact form generated using PyMOL software. AFM experiments are currently underway to analyze the dark-adapted state (Pr) of P3 in order to observe the anticipated structural changes. Ultimately, the goal is to use AFM and other surface analytical methods such as scanning tunneling microscopy and electron microscopy to gain new insight into the unique photochemistry of P3.